Properties of Biochar Obtained from Tropical Crop Wastes Under Different Pyrolysis Temperatures and Its Application on Acidic Soil - Shuhui Song; Ping Cong; Chao Wang; Puwang Li; Siru Liu; Zuyu He; Chuang Zhou; Yunhao Liu; Ziming Yang (Agronomy, 2023)
When biochars are produced, feedstock is a crucial factor that determines their physicochemical properties. However, the characteristics of tropical crop waste-derived biochar have not been described and limit its availability. In this study, pineapple leaf (PAL), banana stem (BAS), sugarcane bagasse (SCB) and horticultural substrate (HCS), were used to prepare biochar at 300, 500 and 700 °C. Properties of biochars and their applications were analysed. The results indicated that hydrophobicity, nonpolarity and aromaticity of SCB biochar (SCBB) were higher than other biochars due to the loss of H (hydrogen), O (oxygen), and N (nitrogen). The pH of PAL biochar (PALB) and BAS biochar (BASB) ranged from 9.69 to 10.30 higher than that of SCBB and HCS biochar (HCSB) with 7.17–9.77. In PALB and BASB, sylvite was the dominant crystal structure. With temperature rising, C–H stretching, C=C stretching and H–O in alcohol groups decreased, and Si–O stretching in HCSB and SCBB strengthened. Biochars obtained at 500 °C, especially SCBB and HCSB, significantly promoted the growth of maize. The PALB and BASB greatly increased the soil pH/EC to 6.90–7.35 and 0.67–0.95 ms/cm, while those of SCBB and HCSB were 5.97–6.74 and 0.23–0.45 ms/cm. The application of the biochars to the soil increased soil pH, reducing the acidic soil stress in maize growth, especially PAL and BAS biochars prepared at 300 °C. Biochar prepared at lower temperature will greatly reduce energy consumption and increase the utilization efficiency of tropical agricultural waste resources.